PENGARUH METODE PEMBAYARAN PAYLATER, COD DAN GRATIS ONGKIR TERHADAP KEPUTUSAN PEMBELIAN DI MARKETPLACE SHOPEE - ASDIANSYURI, ULFIYANI; FARIANTIN, HJ. ERVIVA; OCTAVIA, YUSI FAIZATHUL; SATIAWATI, ELVINA (GANEC SWARA, 2024)
This research aims to determine the influence of the PayLater Payment Method, Cash on Delivery and Free Shipping Promo on Purchasing Decisions at the Shopee Marketplace among STIE AMM Mataram Students. This type of associative research with a population of 201 and a sample of 67, the research population is Active Even Semester Students STIE AMM Mataram. Sampling was purposive sampling of 67 respondents, distributing statements in the form of questionnaires to students, using the data analysis technique used was multiple linear regression using the SPSS20 method. The research results show that: the Pay Later payment method has a positive and significant effect on purchasing decisions with a tcount > t table value, namely 2,571 > 1.99. COD has a positive and significant effect on purchasing decisions with a tcount > table value, namely 3.761 > 1.99 and The free shipping promotion has a positive and significant effect on purchasing decisions with a tcount > table value of 2.770 > 1.99. F calculated has a value greater than F table, namely obtained from F calculated 132.112 with a value of sig = 0.000 which means that all variables have an effect simultaneously.